Comprehensive optimized hybrid energy storage system for long-life solar-powered wireless sensor network nodes. (15th May 2021) - Qi, Nanjian; Yin, Yajiang; Dai, Keren; Wu, Chengjun; Wang, Xiaofeng; You, Zheng
Highlights: A new two-port hybrid diode topology is proposed for solar-powered WSN. An adaptive supercapacitor buffer energy management strategy is designed. The system cost, size, control complexity, and energy loss are decreased. The battery lifetime is increased by at least two times that of the existing HESSs. Abstract: Solar energy harvesting is promising to provide long-term power autonomy for wireless sensor networks. Energy storage devices like lithium-ion batteries are usually integrated to solar-powered sensor nodes to overcome the intermittency of solar power. However, the cycle life of lithium-ion batteries is short, which limits the lifetime of the nodes. Therefore, supercapacitor-battery hybrid energy storage system has been used to extend the cycle life of battery. The design of hybrid energy storage systems significantly affects the performance of wireless sensor network nodes in many ways. However, hybrid energy storage system optimization is a comprehensive problem because the configuration and power-split strategy need to be considered concurrently, which has not been done in the existing studies of solar-powered sensor nodes. In this study, a two-port hybrid diode topology is proposed, accompanied by an adaptive supercapacitor buffer energy management strategy to achieve integrated optimization. The hybrid diode semi-active topology uses a unidirectional DC/DC converter accompanied by two diodes to replace the bidirectional DC/DC converter in the existing semi-active topology. Accordingly, the energy lose is decreased by 15.5% while the cost, size, and controlling complexity are also decreased. Moreover, an adaptive supercapacitor buffer energy management strategy is designed based on the new topology to decrease the battery degradation. Simulation and experimental results indicate that the proposed hybrid energy storage system increases the battery lifetime to at least 3 times that of existing hybrid energy storage systems. Finally, a long-life solar-powered wireless sensor network node with a relatively small size and cost is achievable.